Determinants and prevalence of metabolic syndrome among the adult population in Hargeisa, Somaliland: A community-based cross-sectional study. - Abdeta Muktar Ahmed; Ayanle Suleiman Ahmed; Mohamed Mussa Abdilahi; Abdulkadir Mohamed Nuh (PLoS ONE)
Background Metabolic syndrome (met-s) is a medical condition that includes abdominal obesity, hyperlipidemia, high blood glucose, and high blood pressure. It is associated with a high risk of developing cardiovascular diseases and type 2 diabetes mellitus. The condition was believed to be a challenge mostly faced by developed nations. A few studies conducted showed that met-s is increasing and becoming more common in Africa, where it was considered rare. The study aimed to assess the determinants and prevalence of met-s among the adult population in Hargeisa town, Somaliland, in 2023. Methods A community-based cross-sectional study among 498 adults living in all eight districts of Hargeisa, was carried out from August to September 2023. The sample size was divided proportionally by the number of households in selected sub-districts. Systematic random sampling was employed to select the households in the sub-districts. One adult from each household was selected and assessed. Data were collected using the STEPwise approach of the World Health Organization. The data were analysed using International Diabetic Federation (IDF) criteria for metabolic syndrome with SPSS version 25. Bivariate and multivariate analyses using logistic regression were performed. Result In total, 498 adults participated in the study. The prevalence of met-s was 26.7% in IDF (males 11% vs. females 38.9%). Being of an advanced age of 45-54 years (AOR = 3.6, CI 1.17-11.27), 55-64 years (AOR = 6.1, CI 1.88-19.83), >64 (AOR = 9.1 CI 2.41-34.92), being a woman (AOR = 10.8, CI 5.3-21.8), being overweight or obese (AOR = 4.5, CI 2.5-8), sedentary behavior (AOR = 3.5, CI 1.6-7.5), and lack of physical exercise (AOR = 0.39, CI 0.17-0.88) were significantly associated with met-s. Conclusion The met-s was predominant in our findings. Community-based prevention strategies and actions are necessary if the met-s and its potential consequences are needed to be mitigated.